2004
DOI: 10.1093/ndt/gfh003
|View full text |Cite
|
Sign up to set email alerts
|

Renal hyaluronan accumulation and hyaluronan synthase expression after ischaemia-reperfusion injury in the rat

Abstract: IR injury depresses parameters of renal function, which coincides with an elevated cortical HA content and Has 2 expression. The enhanced Has 2 expression indicates that the cortical HA accumulation is primarily dependent on increased HA synthesis and not impaired degradation/elimination. The water binding and pro-inflammatory properties of HA may contribute to renal dysfunction after IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 19 publications
(35 reference statements)
4
40
0
Order By: Relevance
“…HA has been implicated in several renal diseases, including renal ischemiareperfusion injury (18)(19)(20). We observed that patients with septic shock had a significant increase in urine HA, which was predictive of renal dysfunction and (on unadjusted analyses) in-hospital mortality.…”
Section: Discussionmentioning
confidence: 74%
“…HA has been implicated in several renal diseases, including renal ischemiareperfusion injury (18)(19)(20). We observed that patients with septic shock had a significant increase in urine HA, which was predictive of renal dysfunction and (on unadjusted analyses) in-hospital mortality.…”
Section: Discussionmentioning
confidence: 74%
“…HA in epithelia is restricted to regenerating and proliferating cells, and high levels of HA in simple epithelia acts as an indicator of pathological processes (Tammi et al 2008a). In renal tubular cells, there is normally no HA, but in many disease states and injuries, the HA content increases (Asselman et al , 2005Goransson et al 2004). HA content increases in many cancers that evolve from simple epithelia, like ovarian, colon, and breast cancers, as reviewed recently (Sironen et al 2011b;Tammi et al 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…We also quantitatively assessed mRNA levels of all three isoforms of hyaluronan synthase (HAS) reflecting hyaluronan biosynthesis (44). These proteins are endogenous ligands of TLRs and are released from damaged tissues (5,11,37). It has been previously demonstrated that TLRs, particularly TLR 4, mediate renal ischemia-reperfusion injury (11).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are endogenous ligands of TLRs and are released from damaged tissues (5,11,37). It has been previously demonstrated that TLRs, particularly TLR 4, mediate renal ischemia-reperfusion injury (11). TLRs are upregulated during hypoxia by mechanisms involving HIF-1␣ (16).…”
Section: Discussionmentioning
confidence: 99%